Gerak politik Muhammadiyah dalam Masyumi - Syaifullah, 1960- (Jakarta : Pustaka Utama Grafiti, 1997)
Political behavior of Muhammadiyah, modern Islamic organization, and Masyumi, Islamic political party in Indonesian history, 1945-1960.
Originally presented as the author's thesis (master's--IAIN Syarif Hidayatullah).
Includes bibliographical references (p. [239]-259) and index.
Keywords: Muhammadiyah (Organization); Masyumi; Masyumi (Organization); Islam and politics -- Indonesia; Islam and politics -- Indonesia -- History -- 20th century; Political parties -- Indonesia; Islam -- Indonesia -- Societies, etc; Indonesia -- Politics and government -- 1966-; Indonesia -- Politics and government -- 1950-1966.